2017
DOI: 10.1371/journal.pone.0181160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and mortality before and after implementation of a pediatric sepsis protocol in a limited resource setting: A retrospective cohort study in Bangladesh

Abstract: BackgroundPediatric sepsis has a high mortality rate in limited resource settings. Sepsis protocols have been shown to be a cost-effective strategy to improve morbidity and mortality in a variety of populations and settings. At Dhaka Hospital in Bangladesh, mortality from pediatric sepsis in high-risk children previously approached 60%, which prompted the implementation of an evidenced-based protocol in 2010. The clinical effectiveness of this protocol had not been measured. We hypothesized that implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
1
19
0
5
Order By: Relevance
“…Maitland et al reported an increase in mortality after fluids bolus in African children with severe infection (44). Studies by Kortz et al (Tanzania) and Vekaria-Hirani et al (Naroby) did not observe reduction on mortality after a protocol implementation (34,45). Kortz et al even observed an increase in length of stay after protocol implementation caused by complications of treatment (34).…”
Section: Challenges In Low-middle-income Countriesmentioning
confidence: 98%
“…Maitland et al reported an increase in mortality after fluids bolus in African children with severe infection (44). Studies by Kortz et al (Tanzania) and Vekaria-Hirani et al (Naroby) did not observe reduction on mortality after a protocol implementation (34,45). Kortz et al even observed an increase in length of stay after protocol implementation caused by complications of treatment (34).…”
Section: Challenges In Low-middle-income Countriesmentioning
confidence: 98%
“…Während viele verschiedene Beobachtungsstudien einen positiven Einfluss auf das Outcome der Implementierung dieses Therapiebündels zeigten, war dieser Effekt in anderen Studien weitaus geringer [317,[320][321][322][323][324][325][326][327][328]. Gründe für solche Unterschiede sind nicht immer leicht zu identifizieren, können jedoch mit Selektionsbias, Unterschieden in den Implementierungsstrategien oder Unterschieden in der Handhabung der Kontrollpopulationen zusammenhängen.…”
Section: Therapiebündel Bei Der Behandlung Des Pädiatrischen Schocksunclassified
“…The EvUp also analyzed the results of 4 nonrandomized studies [34][35][36][37] and 1 study protocol. 38 The Society of Critical Care Medicine's Surviving Sepsis Campaign International Guidelines for the Management of Septic Shock and Sepsis-Associated Organ Dysfunction in Children was published in February 2020, 26 immediately before the submission of this publication. In these 2020 surviving sepsis guidelines, recommendations for fluid administration differ based on the availability of intensive care within the system caring for the infant or child.…”
Section: Pals: Recognition and Treatment Of Septic Shock Fluid Adminimentioning
confidence: 99%